The dreamers [large type] : a novel - Walker, Karen Thompson (Random House Large Print, 2019)
One night in an isolated college town in the hills of Southern California, a first-year student stumbles into her dorm room, falls asleep--and doesn't wake up. She sleeps through the morning, into the evening. Her roommate, Mei, cannot rouse her. Neither can the paramedics, nor the perplexed doctors at the hospital. When a second girl falls asleep, and then a third, Mei finds herself thrust together with an eccentric classmate as panic takes hold of the college and spreads to the town. A young couple tries to protect their newborn baby as the once-quiet streets descend into chaos. Two sisters turn to each other for comfort as their survivalist father prepares for disaster. Those affected by the illness, doctors discover, are displaying unusual levels of brain activity, higher than has ever been recorded before. They are dreaming heightened dreams--but of what?